Refugee Politics in the Middle East and North Africa Human Rights, Safety, and Identity - Ullah, A. (Global Ethics, 2014)
Ahsan Ullah provides an insightful analysis of migration and displacement in the Middle East and North Africa. He examines the intricate relationship of these phenomena with human rights, safety concerns and issues of identity crisis and identity formation.